SINGLE-LAYER INTESTINAL ANASTOMOSIS FORMATION OPTION: OPERATIONAL EXPERIENCE - Гривенко С. Г.; Резанов П. О. (World of Medicine and Biology, 2014)
Introduction. One of the most actual issues in abdominal surgery is a creating of optimal conditions for GIT sutures and anastomoses healing. Thereupon the necessity of scrutiny of regeneration morphogenesis regularities is obvious for diverse anastomosis formation techniques. Purpose – to conduct a clinical evaluation of author’s single-layered suture usage in abdominal surgery for GIT anastomoses formation with a study of morphological changes during anastomotic site healing. Materials and Methods. This research is based on a retrospective analysis of 163 patients’ examination and surgical treatment of intraabdominal pathologies with anastomoses formation. Study is conducted in two patients’ cohorts. There were 74 patients in a main cohort, where we used author’s single-layered suture in anastomoses formation (Patents of Ukraine #88732 from 25.03.2014; #94752 from 25.11.2014). Control cohort had included 89 patients with analogous pathology, where we used double-layered suture for anastomoses formation. Discussion. Main cohort demonstrated one complication in an early postoperative period: an anastomositis /1/. Control cohort exhibited following complications: an anastomositis /7/, a bleeding from anastomotic line /1/, a suture dehiscence /1/, an adhesive disease /1/, an intestinal fistula /1/.Macro- and microscopic healing of anastomoses was more favourable in main cohort’s patients. Proposed anastomosis formation technique revealed its justifiability even in circumstances of peritonitis and acute bowel obstruction. Long-term results are traced in 57 patients of the main cohort and 53 patients of control one. Patients of the main cohort had anastomoses disfunction in no case. We didn’t note ligatures, erosions or ulcers also. In 3 patients of the control cohort we revealed anastomoses stenosis of various degrees with affected evacuation. Anastomotic ligatures are revealed in 2 patients of this cohort. Three patients demonstrated deformation and cicatrical stricture of anastomotic site during endoscopy without clinical or roentgenological signs of affected passage. Two patients had anastomotic ligatures combining with signs of chronic anastomositis. Erosive-ulcerous anastomositis is revealed in 2 patients. Usage of proposed technique for single-layered anastomosis formation in abdominal surgery allows to reduce a post-operative complications rate, to improve outcomes and functional results of surgeries. Given anastomoses formation technique facilitates a reduction of inflammatory response and normalizes regeneration processes in an anastomotic site, which is proved by macro- and microscopic examinations.
Keywords: anastomosis; intestinalsuture; complications